2021
DOI: 10.3389/fmed.2021.794599
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Thrombosis Might Develop by COVID-19 Infection or Vaccination: A Systematic Review of Case-Report Studies

Abstract: Background and Objective: Infection by the novel coronavirus disease 2019 (COVID-19) has been associated with different types of thrombotic complications same as portal vein thrombosis (PVT). However, by emerging vaccines of COVID, the thrombosis did not seem to be concerning anymore. Until new findings showed that, the vaccine of COVID itself can cause PVT.Method: We performed an electronic search in PubMed, Scopus, and Web of Sciences to evaluate the possibility of occurring PVT due to infection and vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
1
14
0
3
Order By: Relevance
“…General symptoms like cough and fever are common, but numerous complications like respiratory, cardiovascular, and musculoskeletal issues and thrombosis are less common [ 4 ]. A meta-analysis of 50,466 patients with COVID-19 found that 96.6% of the patients had abnormal CT scans, a finding found in our patient [ 2 , 5 ]. The literature suggests that COVID-19 increases the risk of coagulation abnormalities, particularly venous thromboembolism (VTE), disseminated intravascular coagulation (DIC), deep vein thrombosis (DVT), and portal vein thrombosis (PVT) [ 2 , 6 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…General symptoms like cough and fever are common, but numerous complications like respiratory, cardiovascular, and musculoskeletal issues and thrombosis are less common [ 4 ]. A meta-analysis of 50,466 patients with COVID-19 found that 96.6% of the patients had abnormal CT scans, a finding found in our patient [ 2 , 5 ]. The literature suggests that COVID-19 increases the risk of coagulation abnormalities, particularly venous thromboembolism (VTE), disseminated intravascular coagulation (DIC), deep vein thrombosis (DVT), and portal vein thrombosis (PVT) [ 2 , 6 ].…”
Section: Discussionsupporting
confidence: 67%
“…Coronavirus disease 2019 (COVID-19), which emerged in Wuhan, China, at the end of 2019, has been classified as a pandemic. The virus has impacted nearly 240 million people across the globe, ranging from an asymptomatic carrier state to respiratory symptoms, cardiovascular abnormalities, neuropsychiatric symptoms, hematologic manifestation, particularly portal vein thrombosis (PVT), and multiorgan failure to death [ 1 - 2 ]. The purpose of this report/study is to increase awareness of this rare complication of COVID-19 (PVT).…”
Section: Introductionmentioning
confidence: 99%
“…Venous and arterial thromboembolism can occur in patients with SARS-CoV-2 viral infection because of its high thrombotic potential. Other types of coagulation disorders can be associated such as disseminated intravascular coagulation (DIC) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The portal and mesenteric vein thrombosis are extremely rare complications and unusual main manifestations of COVID-19 developed within 2 weeks from admission. The mechanism of these conditions is the same which leads to the liver injury [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation